(untitled) (Research, Society and Development, 2022)
In this article, compliance with the legal provisions relevant to digital scams committed against the elderly is analyzed, with regard to the explicit rights in the Federal Constitution of 1988 and Law 10.741/03, which guarantee a cluster of rights and fundamental guarantees to the proven class. Thus, the current constitutional text determines that, in its Art. 230, it is not the duty of the State alone, but of society together to ensure the fundamental rights of the elderly. However, such legislative guarantees are continually disregarded, due to the technological naivety of that social class, this fact contributes to the fact that the elderly who do not have technological knowledge are victims of digital scams, which will also be explained.